(untitled) (Indian Journal of Child Health, 2018)
Congenital chloride diarrhea (CCD) is a rare, inherited disorder. Our case was a preterm neonate who presented with severe watery diarrhoea since Day 2 of life. There was maternal history of polyhydramnios and dilated bowel loops. The diagnosis of CCD was confirmed by mutation analysis. The infant is 9 months corrected age, on salt and potassium supplementation, with age-appropriate milestones. The diagnosis of CCD must be made early to prevent life-threatening fluid and electrolyte imbalance.